Peningkatan Kesadaran Hukum Anak Binaan melalui Penyuluhan Hukum tentang Perlindungan Anak dan Sistem Peradilan Pidana Anak di Yayasan Aldyan Citra Insania - Kartika Asmanda Putri; Endang Yuliana Susilawati; Nimas Yuski Nur Laeli (Lembaga Pengembangan Kinerja Dosen, 2026)
Legal awareness is an important aspect in shaping a child's character and preventing the emergence of various forms of delinquency that can lead to legal issues. However, there are still many children who do not understand their rights, obligations, or the legal consequences of their actions. This condition is also found among the children under the care of the Aldyan Citra Insania Foundation, who still have limited understanding of child protection and the Juvenile Criminal Justice System (SPPA). Therefore, this community service activity aims to raise legal awareness among the children in the foundation's care, the foundation's management, and volunteers thru legal counseling and assistance regarding child protection and the Juvenile Criminal Justice System. The method used is a participatory approach with stages of observation, partner needs identification, legal counseling, interactive discussions, consultation, mentoring, and evaluation. The material provided includes legal awareness, children's rights and obligations, child protection, forms of juvenile delinquency along with their legal consequences, as well as mechanisms for resolving juvenile cases thru diversion and restorative justice. The results of the activity show an increase in participants' understanding of the material presented, a heightened concern for child protection, and an improvement in the foundation's administrators' ability to mentor the children in their care. In addition, this activity encourages the growth of a shared commitment to creating a safe, child-friendly environment free from various forms of violence. Legal counseling and assistance provided have proven to be effective means in raising legal awareness while simultaneously strengthening the foundation's capacity to conduct ongoing child guidance and protection.